Management of coronary artery aneurysms using abciximab in children with Kawasaki disease. (1st October 2016) - Bachlava, Evangelia; Loukopoulou, Sophia; Karanasios, Evangelos; Chrousos, George; Michos, Athanasios
Abstract: Introduction: There are limited data regarding the possible benefits of abciximab in children with Kawasaki disease (KD), who developed serious cardiac abnormalities non-responsive to standard treatment. Materials and methods: We retrospectively identified children with KD who were treated with abciximab from 2007 to 2015. Data regarding clinical course, treatment, echocardiographic data and follow-up at 1 and 6 months were retrieved. Results: During the study period, fifteen children were identified who were diagnosed with KD and were given abciximab. The median age at onset of symptoms was 11 months (range: 2 months–6 years). The median day of disease at admission was 10 days (range: 4–26 days) and the median day of administration of abciximab was 17 days (range: 9–40). Twelve children were diagnosed with complete and three with incomplete KD. Aneurysms were found in 8 children: 2 had ectatic coronary arteries and 5 presented with both ectasia and aneurysms. At 1 month follow-up, echocardiographic findings showed regression in the size of aneurysms in 11 children, resolution of the aneurysms or ectasia of coronary arteries in 3 children, while one child who could not take aspirin because of G6PD deficiency died. After 6 months of follow-up, echocardiographic findings showed resolution of coronary abnormalities in 12 (80%) children, whereas 2 children (13.3%) presented with significant regression of aneurysms. Conclusions: Abciximab may have an important role in the management of severe cardiac complications of KD, although prospective randomized controlled studies are needed to fully evaluate its role.